Fine Mapping of qd1, a Dominant Gene that Regulates Stem Elongation in Bread Wheat - Xie, Yongdun; Zeng, Weiwei; Wang, Chaojie; Xu, Daxing; Guo, Huijun; Xiong, Hongchun; Fang, Hanshun; Zhao, Linshu; Gu, Jiayu; Zhao, Shirong; Ding, Yuping; Liu, Luxiang (Frontiers in Genetics, 2021)
Stem elongation is a critical phase for yield determination and, as a major trait, is targeted for manipulation for improvement in bread wheat (Triticum aestivum L.). In a previous study, we characterized a mutant showing rapid stem elongation but with no effect on plant height at maturity. The present study aimed to finely map the underlying mutated gene, qd1, in this mutant. By analyzing an F2 segregating population consisting of 606 individuals, we found that the qd1 gene behaved in a dominant manner. Moreover, by using the bulked segregant RNA sequencing (BSR-seq)-based linkage analysis method, we initially mapped the qd1 gene to a 13.55 Mb region on chromosome 4B (from 15.41 Mb to 28.96 Mb). This result was further confirmed in F2 and BC3F2 segregating populations. Furthermore, by using transcriptome sequencing data, we developed 14 Kompetitive Allele-Specific PCR (KASP) markers and then mapped the qd1 gene to a smaller and more precise 5.08 Mb interval from 26.80 Mb to 31.88 Mb. To develop additional markers to finely map the qd1 gene, a total of 4481 single-nucleotide polymorphisms (SNPs) within the 5.08 Mb interval were screened, and 25 KASP markers were developed based on 10x-depth genome resequencing data from both wild-type (WT) and mutant plants. The qd1 gene was finally mapped to a 1.33 Mb interval from 28.86 Mb to 30.19 Mb on chromosome 4B. Four candidate genes were identified in this region. Among them, the expression pattern of only TraesCS4B02G042300 in the stems was concurrent with the stem development of the mutant and WT. The qd1 gene could be used in conjunction with molecular markers to manipulate stem development in the future.